KAJIAN VISUAL RITUAL NYANGKU MASYARAKAT PANJALU CIAMAIS: Studi bentuk dan makna ritual Nyangku masyarakat Panjalu Ciamis - Soleh, - (2010)
This thesis is arraged based on the research Cnsernedritual visual study Nyangku at Panjalu Ciamis. This research is focused at ritual study Nyangku generally which becomes the culture at Panjalu. The writer regarels thet it is imfortant to explore and study this froblem because there are not specific literature and research pfoof which talk dhis ritual visual research problem Nyangku at Panjalu Ciamis. However, this ritual is done once in a year which cultural inheritauce ritual. A lot af mussmedia give the news a bout this action ritual generallybut but they do not explore the philosophy value and the meaning pf thet ritual Nyangku is hoped can be completed the kuowledge repert ory whitc comes from tradition in Nusantara. And it an be riched the nition culture. In studying and analijing, this re search data uses historical discipline approach. This aspect studies the ritul visual reality, Nyangku is seen form form, meaning and another accessories at Panjalu society Based on this research result can be expressed generally thet ritual Nangku has the similarity with Panjang jimat in Cirebon. This similarity is in the case of the ritual form in taking a bath the heir loom thing and is done at Mulud wonth togetherwith the Ceremony of Maulid prophet Muhamad. Saw. This meaning and symbol are expressed to refer thet there are the causal and integral relationship among heirloom thing, huge cloth, art and another accessories such as umbrella, lanc, bauners and the function in religious Ceremony and sword with the histirical of entering Islam at Panjalu. By this research is hoped thet it will give the know ledge contribution which relates to National Culture historic, especially in west Java.